Environment Friendly Water-Based Drilling Fluid Using Natural Vegetable Gum - Li, Fengxia; Wang, Zhengku; Tian, Yunying; Zhang, Jiyin (Asian Journal of Chemistry, 2013)
This paper reported the formulation and the laboratory analysis of TLJ-1 vegetable gum drilling fluid with the temperature resistance capability up to 140 ºC. Based on the single-factor method, TLJ-1 is chosen as the main treatment agents for the fluid, LV-CMC and PEG taken as the filtrate reducer, QS-2 taken as the rigid filling particles, the three formulations, i.e., the low-solids drilling fluid, the solids-free drilling fluid and the weighting natural vegetable gum drilling fluid have been presented. The laboratory analysis has demonstrated the good temperature resistance capability of the presented TLJ-1 vegetable gum drilling fluids for environmental safety.